Odpowiedzi

2010-03-07T19:31:28+01:00
1+X(X+4) DLA X= -11
-11(-11+4)=-11*(-7)=77

x-2y dla x= 1 y= -1
1-2*(-1)=1+2=3

2e²-y(x+1) dla x= -2 y= 5
2e^-5(-2+1)=2e^+5

(m+1)(n-2) dla m= 2 n= 1
(2+1)(1-2)=3*(-1)=-3
2 5 2
2010-03-07T19:33:50+01:00
1+x(-11+4)=1+(-11)*(-11+4)=1+(-11)*(-7)=1+77=78
2*(-2)^-5(-2+1)=8-5(-1)=8-(-5)=8+5=13
(2+1)*(1-2)=3*(1=(-2))=3*(-1)=-3
mam nadzieje ze pomoglam ;)
1 5 1
Najlepsza Odpowiedź!
2010-03-07T19:35:48+01:00
1+X(X+4) DLA X= -11
1+x²+4x=1+121-44=78

x-2y dla x= 1 y= -1
1-2(-1)=1+2=3

Nie mam ile jest dla e wiec dam dla dwoch opcji x i y.Wydaje mi się, że to pomyłka była.
2e²-y(x+1) dla x= -2 y= 5
2x²-yx-y=8+10-5=13
2y²-yx-y=50-5+13=58

(m+1)(n-2) dla m= 2 n= 1
(2+1)*(1-2)=3*(-1)=-3